ANALISIS PENGARUH SERAT POHON PISANG TERHADAP SIFAT MEKANIK DAN TOPOGRAFI PADA MATRIKS POLYESTER DENGAN 8 JENIS PISANG - Deni deni; Yuliyanto Yuliyanto; Juanda Juanda (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
This research was conducted to obtain data on mechanical ability in the form of tensile strength, impact strength and physical shape of 8 types of banana tree fibers using polyester matrix BQTN 157 with a volume fraction of 85%:15% made by hand lay-up method. The highest tensile voltage of composite fiber-based banana tree fibers random fiber arrangement is in the type of banana kepok with a volume fraction of 85% : 15% of 26.5 Mpa. And for the highest impact strength is on the type of banana kepok of 28.77 Kj/mm². As for the lowest tensile voltage reinforced fiber banana tree arrangement randomly that is on the type of banana honey with a volume fraction of 85% : 15% of 12.18 Mpa. And for the lowest impact force is in the banana type crew with a volume fraction of 85% : 15% of 15.13 Kj/mm²